Characterization of low level viraemia in HIV-infected patients receiving boosted protease inhibitor-based antiretroviral regimens. Issue 4 (3rd September 2019) - Ferretti, Francesca; Mackie, Nicola E.; Singh, Gurmit Kaur Jagjit; Fox, Julie; Kaye, Steve; McClure, Myra O.; Taylor, Graham; Boffito, Marta
Abstract : To understand the pathogenesis of low level viraemia (LLV) in HIV-infected patients on boosted protease inhibitors (PI/b), we enrolled 34 subjects with a median HIV-RNA 79 copies/mL and followed them for 15 months. Samples for next generation sequencing were collected at three time-points. Two showed resistance-associated mutations (RAMs) in the protease gene, while 95–100% had RAMs in the gag gene, which evolved in approximately a quarter of subjects, suggesting a potential clinical role of these kind of mutations.